The Article PERAN DAN FUNGSI KURIKULUM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MULTIKULTURAL - Ramdanil Mubarok (CBJIS : Cross-Border Journal of Islamic Studies, 2021)
This paper was written to want to know what the role and function of the curriculum in multicultural Islamic education will look like. From this paper, it is hoped that it will be able to become a basis for the author to carry out further writing activities. In this paper, the authors formulate: how the role of the curriculum, how the curriculum functions, and how the curriculum is in multicultural Islamic religious education learning. The result is that the role of the curriculum includes: the role of conservative, critical and evaluative, and creative. While the functions of the curriculum include: the function of achieving educational goals, the function of the curriculum for school leaders, the function for education levels, the function for teachers, the function for supervisors, the function for the community, the function for parents, the function for graduate users, the educational function for students. If you pay attention to the function of the curriculum as a process, what needs to be considered is related to the multicultural Islamic religious education curriculum, namely; (1) Status of students (2) Learning styles and student culture, (3) Cultural environment and student personality (4) Student culture and learning resources. In a multicultural context, the function of the curriculum must be related to tolerance, cultural, ethnic, and religious differences.